The "Lost" Country. Why is Georgian History and Culture so Little Known in the English-speaking World? - Peter Skinner, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2014)
In November of 2013 Levan Kiknadze, a Georgian archaeologist, residing in the US, sent an open letter to the editorial board of “The Kartvelologist” journal. He introduced Peter Skinner, an American historian whose illustrated book about the history of Georgia was being prepared for publication. Mr. Kiknadze suggested that we published Skinner’s article and informed us about his disappointment on the fact that English speaking readers hardly know the history of Georgia and had no access to the relevant literature. On my part, I communicated to Mr. Skinner that several important books have been recently published in English in Georgia and international experts in Kartvelian studies published monographs on the history of Georgia in English and German. But we considered it necessary to publish this article after the relevant expert review. The article demonstrates great love for and admiration of rich Georgian culture and its old, heroic history. Though, it also deals with the frustration with the fact that there are very few publications about Georgia in English and they are not available for wide circles of readers. I believe that scholars and cultural professionals should take into account the researcher’s remarks. We should manage to listen to the remarks full of compassion towards us and improve the situation. The article is published both in English and Georgian (translated by Mr. Kiknadze)